Potencialidades e limitações da agropecuária Sul-Mineira na perspectiva de profissionais de ciências agrárias e lideranças de produtores rurais - Espírito Santo, Luciana Souza do (2000)
This piece ofwork seeks understanding on how the professionals of the Agrarian Sciences and the agro-producers' leaderships sense the environment they deal with, thus extracting from it relevant information for setting strategies for the development ofagro-pecuary inthe south ofMinas. For such purpose, we sought theidentification and description ofthefàvorable and limiting factors to the development of agropecuary in the southern region of Minas Gerais as well as the knowledge of how such factors might be used in strategies for regional development During the accomplishment ofthis piece ofwork, it was fbund out that preocupation exists, on behalf of both parts interviewed, concerning the search for ahernatives for the agropecuary development, thus articulating such activhy to fts industrial link, providing for means which will link the producers to the market The following factors have been identifled as fàvorable, in the region: location, edaphoclimatic factors, faydric and touristic potentials. The agricultural disarticulation as well asthe lack ofactive politicians have been identifled as the main limiting factors, thus constituting reasons for the worries of the ones interviewed. Factors related to school institutions, research and extension, to the producers' organizations and the implantation of more agro-industrial piants in the south of Minas, to the globalization of economy were also inthe scope ofthis stuày. It was verified that theknowledge ofthe potencialities and limitations ofthe region, as pointed out by both parts interviewed, are ofgreat importance for the region as they provide for a better notion of the reality involving it, acting as a source of information, for the formularion of feasible strategies for the development of the agropecuary applicablefor the region.